Third User Workshop on High-Power Lasers at the Linac Coherent Light Source. Issue 2 (3rd March 2016) - Bolme, Cindy; Glenzer, Siegfried; Fry, Alan
Abstract : On October 5–6, 2015, the third international user workshop focusing on high-power lasers at the Linac Coherent Light Source (LCLS) was held in Menlo Park, CA, USA [1, 2 ]. The workshop was co-organized by Los Alamos National Laboratory and SLAC National Accelerator Laboratory. More than 110 scientists attended from North America, Europe, and Asia to discuss high-energy-density (HED) science that is enabled by the unique combination of high-power lasers with the LCLS X-rays at the LCLS-Matter in Extreme Conditions (MEC) endstation.